Advances in Conceptual Modeling - Challenges and Opportunities ER 2008 Workshops CMLSA, ECDM, FP-UML, M2AS, RIGiM, SeCoGIS, WISM, Barcelona, Spain, October 20-23, 2008, Proceedings - Song, Il-Yeol; Piattini, Mario; Chen, Yi-Ping Phoebe; Hartmann, Sven; Grandi, Fabio; Opdahl, Andreas L.; Ferri, Fernando; Grifoni, Patrizia; Caschera, Maria Chiara; Rolland, Colette; Woo, Carson; Salinesi, Camille; et al. (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2008)
This book constitutes the refereed joint proceedings of seven international workshops held in conjunction with the 27th International Conference on Conceptual Modeling, ER 2008, in Barcelona, Spain, in October 2008. The 42 revised full papers presented were carefully reviewed and selected from 108 submissions. Topics addressed by the workshops are conceptual modeling for life sciences applications (CMLSA 2008), evolution and change in data management (ECDM 2008), foundations and practices of UML (FP-UML 2008), modeling mobile applications and services (M2AS 2008), requirements, intentions and goals in conceptual modeling (RIGiM 2008), semantic and conceptual issues in geographic information systems (SeCoGIS 2008), and Web information systems modeling (WISM 2008).